Pengaruh Penerapan Supply Chain Resilience terhadap Kepuasan Pelanggan di Terminal Berlian Manyar Sejahtera - Mohammad Arif Rahmadhani; Elly Kusumawati; Vigih Hery Kristanto; Bugi Nugraha (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of the implementation of Supply Chain Resilience(SCR) on customer satisfaction at the Berlian Manyar Sejahtera Terminal, Gresik, which is part of the Java Integrated Industrial and Ports Estate (JIIPE) area. The background of this study is based on the importance of supply chain resilience in ensuring operational continuity, especially in the dynamic and competitive maritime logistics sector. The study uses a quantitative approach with a survey method by distributing questionnaires to terminal service users. The sampling technique used ispurposive sampling, with a total of 30 respondents. The data were analyzed using SPSS software version 27 with a series of statistical tests, including validity, reliability, normality, linearity, heteroscedasticity, simple linear regression, and t test.t. The results of the study show that the implementation ofSupply Chain Resiliencehas a positive and significant effect on customer satisfaction. The regression coefficient value of 0.721 indicates that every one unit increase in SCR will increase customer satisfaction by 0.721 units. In addition, the coefficient of determination (R²) of 0.753 indicates that 75.3% of the variation in customer satisfaction can be explained by the SCR variable. This finding confirms that aspects such as HR readiness, operational flexibility, and coordination and communication in the supply chain have an important role in shaping positive customer perceptions of port services. Thus, increasing supply chain resilience is a key strategy in improving terminal competitiveness.